PENDUGAAN PARAMETER GENETIK DAN HERITABILITAS PADA KARAKTER VEGETATIF CABAI RAWIT GENERASI PERTAMA (M1) HASIL IRRADIASI SINAR GAMMA - Rima Margareta Retnyo Gumelar; Sri Kuning Retno Dewandini; Nailan Nabila; Amalia Nurul Huda (Fakultas Pertanian, Universitas Janabadra, 2023)
Increasing production and yield quality of cayenne pepper can be done by assembling superior varieties through plant breeding programs. Information related to genetic diversity and heritability is very important for establishing a variety. This research aims to obtain information about genetic diversity and heritability values in the vegetative characters of the first generation (M1) cayenne pepper mutant genotype. The research was carried out from May to September 2023 at the Wedomartani Experimental Garden, Faculty of Agriculture, UPN